The Correlation Between Students’ Habit in Watching Movies and Students’ Listening Skill - Risca Nur Qodariah; Nurhasanah; Nopa Yusnilita (JOLE (Journal of Language Education), 2024)
The habit of watching English movies provides an opportunity to practice our listening skills, can practice our intonation pronunciation to be better then can learn accents in English get new vocabulary and gain cultural insight. The aim of this study is to find out: the correlation between students' habits in watching English movies and listening skills of students of English Education Study Program at Baturaja University. This study focused on finding and knowing the correlation between students' habits in watching English movies and listening skills of second semester students of Baturaja University. This type of research is quantitative. In collecting data, researchers used questionnaires and tests. The population of this study were students of English education study program of Baturaja University. The research sample is the second semester students of English education study program of Baturaja University. The sample of this study consisted of 26 students. The sampling method in this study was purposive sampling. The technique of collecting data on students' habits in watching English movies using a questionnaire. The technique of collecting data on listening skills using the English book by Jack C.Richards (2010). Data analysis technique using Pearson Product Moment correlation. The research findings show that there is a positive correlation between students' habits in watching English movies and English listening skills in the second semester of the English language education study program at Baturaja University where rxy = 0.801 is obtained. So, the alternative hypothesis (Ha) is accepted and null hypothesis (Ho) is refused. Therefore, it can be concluded that students' habits in watching English movies and listening skills are in the very strong category.